Gold Nanoparticle Enhanced Electrochemical Assay for Protein Kinase Activity Using a Synthetic Chemosensor on a Microchip. Issue 4 (6th February 2015) - Chand, Rohit; Han, Dawoon; Shin, Ik-Soo; Hong, Jong-In; Kim, Yong-Sang
Abstract : Phosphorylation by protein kinases is a predominant form of protein regulation. Abnormal phosphorylation of protein is linked to several medical conditions. In this paper, we report a disposable electrochemical microchip for protein kinase activity assay based on a synthetic chemosensor. The approach involves the phosphate-specific chemosensors linked to gold nanoparticles, anchored on an electrochemical sensor fabricated on the plastic film, and the enzyme substrate labeled with ferrocene tag. In the presence of protein kinase, the substrate undergoes phosphorylation, which subsequently binds to the chemosensor, and then the ferrocene tag of the enzymatic product generates strong oxidation current under voltammetry. Gold nanoparticles were employed as a bridge between the electrode and chemosensor, which significantly enhanced the current signal. A limit of detection of the enzyme was estimated to be 0.05 U/mL with a linear dynamic range between 2–50 U/mL. Furthermore, the interference and inhibition studies were also successfully carried out using this strategy. The method proposes the potential for application in the development of a kinase assay system.